Impact of the War in Croatia (1991-1995) on the Differentiation of Age Structure between Serbs and Croats: A Case Study of the Banija Region - Kovjanić, Aleksandar; Pavlović, Mila; Živanović, Vedran; Krstić, Filip (Nationalities papers, 2023)
Aging is the subject of various studies by the scientific community and monitoring by responsible institutions. The intensity of aging and the proportion of age groups among various communities differ due to different socio-economic conditions and characteristics. This article researches the impact of the war in Croatia 1991–1995 and postwar living conditions on the divergence of population aging in the ethnically heterogeneous Banija region. The first postwar census in 2001 recorded a population decline of 44.9% compared to the 1991 census. We analyze the effects of the war on changes in ethnic and age structure, as well as their interrelations. The quantitative and qualitative magnitude of these demographic changes in the inter-census period had a decisive influence on the correlation of age and ethnic structure. The article examines whether the relative share of Serbs or Croats in the total population of a settlement affects the average age of the settlement. The results confirmed that the Serbs are older than the Croats, and are in the phase of the most advanced demographic age. These changes raise the question of the demographic future and the biological viability of the Serbs, who were the majority in the region before the war.